Pengaruh Lingkungan Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Tifico Fiber Indonesia, Tbk. Di Tangerang - Khaikal Furqon Nugroho; Aden Prawiro Sudarso (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. This study aims to determine the effect of work environment and work stress on employee performance at PT Tifico Fiber Indonesia, Tbk. in Tangerang, both partially and simultaneously. This research uses a quantitative associative method. The sampling technique was conducted using the slovin formula with a total sample of 83 respondents. Data analysis techniques include data instrument testing, classical assumption tests, simple and multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing using the t-test and F-test. The results show that the work environment partially has a positive and significant effect on employee performance, as indicated by the simple linear regression equation Y = 18.214 + 0.487X1. The correlation coefficient value is 0.681, indicating a strong relationship, with a coefficient of determination of 46.4%. The t-test results show that tcount > ttable (6.112 > 1.670) with a significance value of 0.000 < 0.05. Work stress partially has a negative and significant effect on employee performance, as indicated by the simple linear regression equation Y = 32.705 – 0.529X2. The correlation coefficient value is –0.592 with a coefficient of determination of 35.0%, and the t-test results show that tcount > ttable (5.038 > 1.670) with a significance value of 0.000 < 0.05. Simultaneously, work environment and work stress have a significant effect on employee performance, as indicated by the multiple linear regression equation Y = 21.436 + 0.361X1 – 0.412X2. The correlation coefficient value is 0.742 with a coefficient of determination of 55.0%. The F-test results show that Fcount > Ftable (48.215 > 3.11) with a significance value of 0.000 < 0.05, therefore Ha is accepted and Ho is rejected.